RELATIONSHIP BETWEEN 35 MEGAPASCAL COMPRESSIVE STRENGTH AND FLEXURAL STRENGTH - Oki Permana; Pio Ranap Tua Naibaho; Sempurna Bangun (International Journal of Civil Engineering and Infrastructure, 2023)
In the modern era like now in the construction sector, there are so many innovations in infrastructure along with the times. Concrete is an important factor in the construction sector with a function as one of the formers of the upper and lower structures. Concrete material is the result of a mixture of cement, coarse aggregate, fine aggregate, water and sometimes added materials with various kinds of innovations. The method used in this study is experimental, by making the test specimen laboratory samples by using two different specimens but with the same quality of concrete is fc'35 MPa. Based on the results of the values on the flexural and compressive test specimens in the laboratory, an unsuitable relationship between flexural strength (has been obtained fs) and compressive strength (fc ') according to SNI 2847: 2013. On formulas (fr = 0.62 √fc′) applis to the concrete test 28 day.